Surface modification of malachite with tetraamminecopper (II) and its effect on sulfidation flotation. (November 2022) - Zhang, Hongliang; Zhou, Qiqi; Lin, Shangyong; Zhang, Chenyang; Sun, Wei; Chen, Daixiong; Wang, Rong; Liu, Mengfei; Chen, Jianhua
Graphical abstract: Highlights: The pretreatment with [Cu(NH3 )4 ] 2+ significantly improved the malachite recovery. [Cu(NH3 )4 ] 2+ can achieve better performance than NH4 + at much lower concentration. The S 2− ions chemisorbed on the malachite surface to form a layer of Cu-S species. Abstract: In view of the strong hydrophilicity of malachite, the sulfidation performance of conventional sulphidizing reagent sodium sulfide on malachite is not satisfactory. In this work, we discussed the effect of tetraamminecopper (II) complex pretreatment on the sulfidation and flotation behavior of malachite. The performance was evaluated by micro-flotation experiments. The flotation results showed that a better flotation recovery can be obtained with a molar concentration of tetraamminecopper (II) sulfate of only one-twentieth of the conventional activator (NH4 )2 SO4, all else being equal. Scanning Electron Microscope with Energy Dispersive Spectrometer (SEM-EDS) shows that the weight percentage of S and Cu on the surface of the sulfidized malachite increased significantly in the present of [Cu(NH3 )4 ] 2+ . The FTIR and Raman results showed that sulfur ions could be chemisorbed on the surface of malachite and form a layer of copper-sulfide species. X-ray photoelectron spectroscopy (XPS) further confirmed the actual existence of the sulfide layer, which consists of monosulfide (S 2− ), disulfide(S2 2− ) and polysulfide (Sn 2− ). The presence of the activator [Cu(NH3 )4 ] 2+ can significantly increase the formation of disulfide and polysulfide on the surface of malachite, thereby promoting the subsequent interfacial adsorption of xanthate.